Identification of human temporomandibular joint fibrocartilage stem cells with distinct chondrogenic capacity. Issue 6 (June 2020) - Bi, R.; Yin, Q.; Mei, J.; Chen, K.; Luo, X.; Fan, Y.; Zhu, S.
Summary: Objective: This study was aimed to identify the residence of human fibrocartilage stem cells (hFCSCs), characterize their stem cell properties and investigate the functional mechanisms which regulate fibrocartilage stem cells (FCSCs) toward chondrogenic differentiation during cartilage homeostasis and repairing. Methods: Cytological characteristics of hFCSCs and human orofacial mesenchymal stem cells (hOFMSCs) were analyzed. Chondrogenic potential of hFCSCs was compared with hOFMSCs both in vitro and in vivo . Regulatory role of SOX9 during FCSCs chondrogenesis was studied by shRNA interference in vitro, and by GFP + FCSCs treatment in rat condylar cartilage defect model. SOX9 expression was also examined in temporomandibular joint osteoarthritis (TMJOA) patients' cartilage surface. Results: hFCSCs exhibited typical mesenchymal stem cell characteristics, with significantly stronger chondrogenic capability compared to hOFMSCs. Moreover, hFCSCs showed remarkably increased expression of SOX9. During cartilage pellet culture, there was stronger SOX9 expression in hFCSCs than hOFMSCs . SOX9 shRNA interference downregulated chondrogenic capability of hFCSCs in vitro, as well as disrupting migration and chondrogenic differentiation of GFP + FCSCs toward mature chondrocytes in rat condylar cartilage defect. Of note, SOX9 expression was also found suppressed in the condylar superficial zone of TMJOA patients. Conclusion: We found the existence of FCSCs in human TMJ cartilage, and characterized their distinct stem cell features. SOX9 is essential for hFCSCs chondrogenic differentiation, and a comprehensive understanding of the regulatory role of SOX9 in hFCSCs would be important for exploring potential intervention strategy of condylar cartilage degradation during TMJ disorders.